The Value of CT Three-Dimensional Reconstruction in Nursing and Diagnosis of Senile Hip Fracture. (20th August 2021) - Shi, Yuanyuan; Chen, Si; Chen, Xue; Xue, Pan
Abstract : Aim. To study the diagnostic effect of hip fracture in the elderly. In this paper, a total of 100 elderly patients with hip fracture from January 2020 to May 2021 were selected for X-ray and CT examination after admission. The operation was taken as the final criteria for determining hip fracture type, and the diagnosis of hip fracture by CT three-dimensional reconstruction was analyzed and studied. The results showed that the diagnostic rate of CT 3D reconstruction for various types of hip fracture in the elderly was higher than that of CT plain scan and X-ray (P < 0.05 ). For the diagnosis of intra-articular small bone fragments, the rate of missed diagnosis was 2% (2/100) with CT 3D reconstruction, 10% (10/100) with conventional CT scan, and 20% (20/100) with X-ray. The rate of misdiagnosis was 5.0% (5/100) with CT 3D reconstruction. Routine CT scan was 15% (15/100), X-ray was 30% (30/100), and CT 3D reconstruction was significantly lower than other examinations (P < 0.05 ). Conclusion . CT 3D reconstruction has high accuracy in the diagnosis of various types of hip fractures in the elderly.